The application of ion-exchange resins in hydrogenation reactions - Uyi Osazuwa, Osarieme; Sumaiya, Zainal Abidin (Springer Nature, 2019)
Reaction processes with minimal energy consumption and potentials to generate renewable energy, alongside dynamism in catalyst functionality, are the driving force behind the use of ion-exchange resins and more specifically, heterogeneous ion-exchange resins over homogeneous catalysts. For hydrogenation reactions, ion-exchange resins have mainly been employed as a catalyst support. The synthesis entails mplanting/impregnating metallic ions into the ion-exchange resin matrix. The major disadvantage of the ion-exchange resin is its low thermal stability which makes the resin disadvantageous for some specific types of reactions. Research is still ongoing toward obtaining resins able to withstand extreme temperature (above 200 °C). This chapter summarizes some selected applications of hydrogenation reactions using ion-exchange resins as catalyst support material. Some of its applications include hydrodesulphurization, hydrodenitrification, and hydrodechlorination which have been reviewed in this chapter.